Effect of Hydrostatic Pressure on the Revers Gate-Current of AlGaN/GaN HEMTs - Yahyazadeh, Rajab; Hashempour, Zahra (International Journal of Integrated Engineering, 2021)
In this paper, we present an analytical-Numerical model for reverse gate leakage current in AlGaN/GaN high electron mobility transistors, which investigate the influence of the hydrostatic pressure (HP) on gate-current.  It has been found that the bound charge at the heterointerface has the most impact on the threshold voltage. The increases in hydrostatic pressure cause an increase in threshold voltage. With increasing HP, the Schottky barrier height decreases, AlGaN electric field and reverse gate leakage current are increased. The increase in HP acts as a positive virtual gate. The dependence on the HP of Poole- Frenkel emission (FP) and Fowler-Nordheim (FN) direct tunneling is more than trap-assisted-tunneling (TAT). Increasing the pressure of 2GPa, the intersection point of PF and TAT varies by 1 volt, and the PF range increases compared to TAT.